Ecosystem Effects of Variant Rabbit Hemorrhagic Disease Virus, Iberian Peninsula - Miguel Delibes‐Mateos; Catarina Ferreira; Francisco Carro; Marco A. Escudero; Christian Gortázar (2014)
To the Editor: In this investigation, we found evidence for the apparent effects that a new variant of the rabbit hemorrhagic disease virus (RHDV) is having on native wild European rabbit (Oryctolagus cuniculus) populations on the Iberian Peninsula, and how this virus could threaten the conservation of endangered predators.